Can the surface electrocardiogram be used to predict myocardial viability?. Issue 6 (1st December 1999) - Al-Mohammad, A; Norton, M Y; Mahy, I R; Patel, J C; Welch, A E; Mikecz, P; Walton, S
Abstract : OBJECTIVE: To investigate whether QRS morphology on the surface ECG can be used to predict myocardial viability. DESIGN: ECGs of 58 patients with left ventricular impairment undergoing positron emission tomography (PET) were studied. 13 N-Ammonia (NH3 ) and 18 F-fluorodeoxyglucose (FDG) were the perfusion and the metabolic markers, respectively. The myocardium is scarred when the uptake of both markers is reduced (matched defect). Reduced NH3 uptake with persistent FDG uptake (mismatched defect) represents hibernating myocardium. First, the relation between pathological Q waves and myocardial scarring was investigated. Second, the significance of QR and QS complexes in predicting hibernating myocardium was determined. RESULTS: As a marker of matched PET defects, Q waves were specific (79%) but not sensitive (41%), with a 77% positive predictive accuracy and a poor (43%) negative predictive accuracy. The mean size of the matched PET defect associated with Q waves was 20% of the left ventricle. This was not significantly different from the size of the matched PET defects associated with no Q waves (18%). Among the regions associated with Q waves on the ECG, there were 16 regions with QR pattern (group A) and 23 regions with QS pattern (group B). The incidence of mismatched PET defects was 19% of group A and 30% of group B (NS). CONCLUSIONS: Q waves are specific but not sensitive markers of matched defects representing scarred myocardium. Q waves followed by R waves are not more likely to be associated with hibernating myocardium than QS complexes.